Requirements for Collaboration With Schools: Public and Private Leaders Speak Out - Kathryn S. Whitaker; Richard A. King; James A. Lowham; Mary Norby-Loud; Paul Sueltenfuss (Educational Considerations, 1993)
If organizations are truly to collaborate, rather than merely cooperate, there will necessarily be a sacrifice of autonomy as they share visions, resources, decisions, and accountability.